SELF-DISCLOSURE OF UNDERGRADUATE STUDENTS WITH MENTAL ILLNESS - Manafe, Rizky Pradita; Mita, Tesa Lolia; Damayanti, Yeni (Journal of Health and Behavioral Science, 2025)
The rising incidence of suicide among students highlights the urgent need to address mental health issues within this group. The primary challenges are that many students hesitate to seek professional help and are unwilling to speak up about their condition. Self-disclosure is one of the factors that can help students deal with mental health problems. This study aims to determine the factors that influence undergraduate students with mental disorders (MDGJ) to do self-disclosure. This study is a qualitative study. The participants in this study were 9 students who were willing to do follow-up interviews after screening. The data collection technique used was semi-structured interviews. Data analysis used thematic analysis. The results of the study found that there were two factors that influenced MDGJ self-disclosure, namely inhibiting and supporting factors. Inhibiting factors consist of family neglect and cognitive distortion, while supporting factors consist of peer support and attempts to seek help. The implication of this study is to provide interventions, such as forming peer counsellors.